LINGO3 regulates mucosal tissue regeneration and promotes TFF2 dependent recovery from colitis. (3rd July 2021) - Zullo, Kelly M.; Douglas, Bonnie; Maloney, Nicole M.; Ji, Yingbiao; Wei, Yun; Herbine, Karl; Cohen, Rachel; Pastore, Christopher; Cramer, Zvi; Wang, Xin; Wei, Wenjie; Somsouk, Ma; et al.
Abstract: Aim: Recovery of damaged mucosal surfaces following inflammatory insult requires diverse regenerative mechanisms that remain poorly defined. Previously, we demonstrated that the reparative actions of Trefoil Factor 3 (TFF3) depend upon the enigmatic receptor, leucine rich repeat and immunoglobulin-like domain containing nogo receptor 2 (LINGO2). This study examined the related orphan receptor LINGO3 in the context of intestinal tissue damage to determine whether LINGO family members are generally important for mucosal wound healing and maintenance of the intestinal stem cell (ISC) compartment needed for turnover of mucosal epithelium. Methods and Results: We find that LINGO3 is broadly expressed on human enterocytes and sparsely on discrete cells within the crypt niche, that contains ISCs. Loss of function studies indicate that LINGO3 is involved in recovery of normal intestinal architecture following dextran sodium sulfate (DSS)-induced colitis, and that LINGO3 is needed for therapeutic action of the long acting TFF2 fusion protein (TFF2-Fc), including a number of signaling pathways critical for cell proliferation and wound repair. LINGO3-TFF2 protein-protein interactions were relatively weak however and LINGO3 was only partially responsible for TFF2 induced MAPK signaling suggesting additional un-identified components of a receptor complex. However, deficiency in either TFF2 or LINGO3 abrogated budding/growth of intestinal organoids and reduced expression of the intestinal ISC gene leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5), indicating homologous roles for these proteins in tissue regeneration, possibly via regulation of ISCs in the crypt niche. Conclusion: We propose that LINGO3 serves a previously unappreciated role in promoting mucosal wound healing.